This great humanity has said : 'enough'! (OSPAAAL (Organization of Solidarity with the People of Asia, Africa and Latin America), 1968)
Enlarged logo of OSPAAAL (Organization of Solidarity with the People of Asia, Africa and Latin America), coloured in red, yellow, brown and black Poster advertising international week of tricontinental solidarity, January 3rd to 10th, 1968 PO-1444